MnO / Cu / C composite material and preparation method and application thereof
Through a step -by -step roasting reaction Legal MNO/CU/C composite material, the problem of low -electrical conductivity and cycle stability in water -based zinc ion batteries in water -based zinc ion batteries is solved. Stable electrochemical properties.
Patent Information
- Application Number
- CN202411639866.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-18
- Publication Date
- 2025-01-28
AI Technical Summary
Manganese-based materials have problems such as low conductivity, large volume changes, and poor cycle stability in aqueous zinc ion batteries, resulting in a decrease in specific capacity and poor cycle life.
The MNO/CU/C composite material is prepared by a one -step roasting reaction legal system. The thermal treatment of the copper -based parts and the manganese -based mathematically forms a nano -active ingredient of carbon coverage, and the electrical and active sites of the material are improved.
Improved the electrochemical properties of the MNO/CU/C composite material, showing high -mortivity performance, high ratio capacity, good cycle stability and high -tech rate.
Smart Images

Figure CN119381437A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a MnO / Cu / C composite material and a preparation method and application thereof, belonging to the technical field of aqueous zinc ion battery material preparation. Background Art
[0002] Aqueous zinc-ion batteries (ZIBs) have become a new type of energy storage device with great development prospects due to their high energy density, high safety and reliability, and economic and environmental protection. Among the many cathode materials, manganese-based materials have become very promising cathode materials due to their high energy density, high safety, low cost, eco-friendliness and non-toxicity. However, manganese-based materials have low conductivity, large volume changes during charging and discharging, easy collapse during the cycle, and irreversible phase change, which causes their specific capacity to drop rapidly, and the cycle life and rate performance are poor, resulting in a large capacity attenuation of the corresponding negative electrode materials.
[0003] Composite materials are made by optimizing the combination of material components with different properties. They have structural designability and comprehensive performance, and can comprehensively play the advantages of various component materials. They are an effective way to optimize manganese-based materials. The combination of MnO materials and carbon-based materials is a hot topic in current research. Carbon can provide high conductivity and buffer framework for composite materials.
[0004] The Chinese patent (CN110085447A) uses an electrospinning method to construct a Cu-MnO / carbon nanofiber composite material. The good solvent N,N-dimethylformamide used is a high-cost, difficult to degrade, and volatile solvent, and it also poses a potential threat to human health. In addition, after the spinning solution is prepared, a precursor must be prepared and then calcined to obtain a carbon nanofiber composite material. The entire preparation process is relatively complicated and involves multiple chemical and physical treatment steps, such as the preparation of the precursor and the calcination treatment, which increase the complexity and cost of the process. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, one of the objects of the present invention is to provide a MnO / Cu / C composite material, in which carbon-coated nano-active ingredients (manganese oxide and copper) are present, the material has many active sites and good conductivity, and has a large comparative area, which helps to improve the electrochemical performance.
[0006] The second object of the present invention is to provide a method for preparing a MnO / Cu / C composite material. The method is prepared by a one-step calcination reaction, has simple steps, uses cheap and readily available raw materials, and has a controllable ratio and strong practicality, which is of great significance for the development of high-performance aqueous zinc ion batteries.
[0007] The third object of the present invention is to provide a MnO / Cu / C composite material for use as a cathode material for an aqueous zinc ion battery. The composite material is used as a cathode material for an aqueous zinc ion battery, and exhibits excellent electrochemical properties, such as good rate performance, high specific capacity, good cycle stability, and high conductivity.
[0008] In order to achieve the above object, the present invention provides a MnO / Cu / C composite material, which is composed of carbon-coated nano-active components, and the nano-active components are composed of nano-copper particles and nano-manganese oxide particles.
[0009] In a preferred embodiment, the ratio of the nano copper particles to the nano manganese oxide particles is measured according to a molar ratio of copper to manganese elements of 1:3 to 1:11.
[0010] In a more preferred embodiment, the ratio of the nano copper particles to the nano manganese oxide particles is measured according to a molar ratio of copper to manganese elements of 1:5 to 1:8.5.
[0011] In a preferred embodiment, the particle size of the nano copper particles is 10 to 70 nm, and the particle size of the nano manganese oxide particles is 10 to 120 nm.
[0012] The present invention also provides a method for preparing a MnO / Cu / C composite material. In an inert atmosphere, a copper-based complex and a manganese-based complex are ground and mixed, and then heat treated to obtain the MnO / Cu / C composite material.
[0013] The key technical point of the present invention is to prepare MnO / Cu / C composite materials by using copper-based complexes and manganese-based complexes as raw materials, mainly the formation body copper ions in the copper-based complexes are converted into copper simple substance after heat treatment, and the copper simple substance has excellent electrical conductivity, which can further improve the material carrier transfer rate, and at the same time, it forms a heterogeneous structure, further increases the active sites, and helps to reduce the energy barrier of zinc embedding, thereby promoting the embedding / de-embedding behavior of zinc ions, and its staggered stable internal network structure achieves excellent cycle stability and rate performance. The central body manganese ion in the manganese-based complex can be converted into MnO after heat treatment. MnO is the core of the active material, and its small size and good dispersibility make it show more active sites, and it shows more excellent zinc storage capacity as a cathode material. At the same time, the present invention heat treats the copper-based complex and the manganese-based complex by a one-step method. During the heat treatment process, the MnO / Cu / C composite material can be formed in one step, and the composite material presents a carbon-coated structure, which is beneficial to the improvement of the cycle stability of its zinc storage process. The ratio of Cu to MnO in the preparation method is easy to control, the preparation steps are simple, and the obtained composite material exhibits excellent electrochemical properties when used to prepare zinc ion batteries, such as high cycle performance and conductivity.
[0014] In a preferred embodiment, the copper-based complex is selected from copper oxalate and / or copper acetylacetonate.
[0015] In a preferred embodiment, the manganese-based complex is manganese acetylacetonate.
[0016] In the copper-based complex and manganese-based complex provided by the invention, the ligand part is transformed into a carbon layer during heat treatment, and the formed body can be transformed into MnO and single substance Cu in one step to construct a MnO / Cu / C composite material.
[0017] According to a preferred embodiment, the copper-based complex is copper acetylacetonate, and the manganese-based complex is manganese acetylacetonate.
[0018] In a preferred embodiment, the molar ratio of the copper-based complex to the manganese-based complex is 1:3 to 1:11. By adjusting the ratio of the copper-based complex to the manganese-based complex of the present invention, the ratio of Cu and MnO in the obtained product can be effectively regulated. The introduction of copper in the composite material helps to further improve the conductivity of the material as a whole. MnO is the core of the active material, and its content directly affects the specific capacity of the overall composite material. The inventors have found through research that the MnO / C composite material prepared by only using the manganese-based complex has a current density of 0.1 A g -1 When the content of MnO is too low, the overall specific capacity of the material is low. Therefore, the molar ratio of the copper-based complex to the manganese-based complex is further preferably 1:5 to 1:8.5.
[0019] In a preferred embodiment, the inert atmosphere is a nitrogen atmosphere and / or an argon atmosphere.
[0020] In a preferred embodiment, the heat treatment conditions include: 3 ~ 15 ℃ min -1 The temperature is raised to 550~750℃ at a heating rate of 100℃ and kept at this temperature for 1~4 hours. If the heat treatment temperature is too low, carbonization will not be complete. If the temperature is too high, other substances will be generated and the yield will be reduced.
[0021] According to a preferred specific embodiment, the method further comprises: cooling the product obtained after the heat treatment to room temperature naturally, washing it with deionized water in sequence, and drying it to obtain the MnO / Cu / C composite material.
[0022] In a preferred embodiment, the drying conditions include: a temperature of 50 to 100°C and a time of 5 to 24 hours.
[0023] In a preferred embodiment, the average particle size of the mixture obtained after grinding and mixing is 0.05 μm to 0.1 μm.
[0024] The present invention also provides a MnO / Cu / C composite material used as a cathode material for an aqueous zinc ion battery.
[0025] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:
[0026] (1) The present invention prepares the composite material by a one-step calcination reaction. The method has simple steps, uses cheap and readily available raw materials, is highly practical, and is of great significance for the development of high-performance aqueous zinc-ion batteries.
[0027] (2) The present invention realizes the composite of MnO with Cu and C by one-step calcination of copper-based complexes and manganese-based complexes. This method can not only effectively improve the performance of the MnO / Cu / C composite material, but also effectively regulate the ratio of the product.
[0028] (3) In the MnO / Cu / C composite material provided by the present invention, the introduction of copper further improves the electrical conductivity of the material. At the same time, the carbon coating structure formed can effectively alleviate the volume change and manganese dissolution problems during the charge and discharge process of the material, which helps to improve the cycle performance of the MnO / Cu / C composite material.
[0029] (4) The MnO / Cu / C composite material provided by the present invention is used as a cathode material in an aqueous zinc ion battery, which exhibits excellent electrochemical properties, such as good rate performance, high specific capacity, good cycle stability, and high electrical conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a SEM image of the MnO / Cu / C composite material prepared in Example 1 of the present invention;
[0031] Figure 2 is the XRD diagram of the MnO / Cu / C composite material prepared in Example 1 and Example 2 of the present invention;
[0032] Figure 3 is a BET diagram of the MnO / Cu / C composite material prepared in Example 2 of the present invention;
[0033] Figure 4 This is a cycle performance analysis diagram of the MnO / Cu / C composite material prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0034] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0035] In the present invention, room temperature refers to 25±2°C.
[0036] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited to the following specific embodiments. Obviously, the embodiments described below are only a part of the embodiments, and all other embodiments obtained by professionals in this field without creative work still belong to the protection scope of the present invention.
[0037] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0038] Example 1
[0039] 0.1560 g of copper acetylacetonate and 0.7 g of manganese acetylacetonate were mixed and ground thoroughly until the average particle size of the mixture was 0.09 μm. The mixture was then transferred to a small porcelain boat and placed in a tube furnace. Under argon atmosphere, the mixture was heated at 5 °C min -1 The temperature was raised to 650 °C and maintained for 2 h. The product was allowed to cool naturally to room temperature. The material was then washed several times with deionized water and finally dried at 80 °C for 12 h to obtain the MnO / Cu / C composite material.
[0040] The present invention exemplarily provides the SEM image and XRD image of the MnO / Cu / C composite material prepared in Example 1, which are shown in Figure 1 and Figure 2 ,from Figure 1 It can be seen that the MnO / Cu / C composite material has a carbon-coated structure, which not only provides high active sites, but also helps to buffer volume changes during the charge and discharge process, thereby improving the cycle stability and electrochemical performance of the material. Figure 2 Analysis shows that the composite material contains characteristic diffraction peaks of elemental copper and MnO. The particle sizes of nano-copper particles and nano-manganese oxide particles were calculated using the Scherrer formula. The particle sizes of the nano-copper particles were 22.8 nm and the particle size of the nano-manganese oxide particles was 20.0 nm.
[0041] Example 2
[0042] 0.0867 g of copper acetylacetonate and 0.7 g of manganese acetylacetonate were mixed and ground thoroughly until the average particle size of the mixture was 0.09 μm. The mixture was then transferred to a small porcelain boat and placed in a tube furnace. Under argon atmosphere, the mixture was heated at 10 °C min -1 The temperature was raised to 700 °C, maintained for 1.5 h, and naturally cooled to room temperature. The material was then washed with deionized water and dried at 70 °C for 16 h to obtain a powdered MnO / Cu / C composite material.
[0043] The present invention exemplarily provides an XRD pattern of the MnO / Cu / C composite material prepared in Example 2, specifically see Figure 2 ,from Figure 2 It can be seen that the MnO / Cu / C composite material obtained in Example 2 has characteristic peaks of Cu and characteristic peaks of MnO. By comparing the characteristic diffraction peaks of copper, it can be seen that the copper content in Example 2 is reduced. The particle sizes of the nano-copper particles and the nano-manganese oxide particles are calculated by the Scherrer formula, and the particle size of the obtained nano-copper particles is 27.9 nm, and the particle size of the nano-manganese oxide particles is 24.4 nm.
[0044] Example 3
[0045] 0.0645 g of copper acetylacetonate and 0.7 g of manganese acetylacetonate were mixed and ground thoroughly until the average particle size of the mixture was 0.09 μm. The mixture was then transferred to a small porcelain boat and placed in a tube furnace. Under argon atmosphere, the mixture was heated at 5 °C min -1 The temperature was raised to 650 °C, maintained for 2 h, and naturally cooled to room temperature. The material was then washed with deionized water and finally dried at 80 °C for 12 h to prepare a MnO / Cu / C composite material.
[0046] The present invention exemplarily provides a BET diagram of the MnO / Cu / C composite material prepared in Example 3, Figure 3 The specific surface area analysis shows that the specific surface area of the MnO / Cu / C composite material is approximately 427.7 cm 2 g -1 , indicating that the material has a large specific surface area, which helps to improve its electrochemical performance.
[0047] Example 4
[0048] This example is carried out in a similar manner to that of Example 3, except that in this example, copper acetylacetonate is replaced with an equal mass of copper oxalate.
[0049] Comparative Example 1
[0050] This comparative example was carried out in a similar manner to Example 3, except that the mass of manganese acetylacetonate was adjusted to 0.216 g in this comparative example.
[0051] Comparative Example 2
[0052] 0.5 g of manganese acetylacetonate was mixed and fully ground to an average particle size of 0.09 μm. The mixture was then transferred to a small porcelain boat and placed in a tube furnace. The mixture was heated at 5 °C min under an argon atmosphere. -1 The temperature was raised to 650 °C and maintained for 2 h. The product was allowed to cool naturally to room temperature. The material was then washed several times with deionized water and finally dried at 80 °C for 12 h to obtain the MnO / C composite material.
[0053] Test Case
[0054] The composite material obtained in the above example was subjected to electrochemical zinc storage performance test and AC impedance test.
[0055] Test method: The composite material was mixed with acetylene black and PVDF in a mass ratio of 70:20:10 (total mass was 0.8735 g), 0.4112 g NMP (N-methyl-2-pyrrolidone) was added, and after mixing evenly, the obtained slurry was evenly coated on a thin stainless steel mesh with a diameter of 14 mm with a scraper. After vacuum drying at 60 °C for 12 h, the slurry was pressed on a tablet press at a pressure of 15 MPa to prepare a working electrode. Then, the metal zinc sheet was used as the anode and the prepared composite material was used as the cathode to assemble the aqueous ZIBs battery and test its performance at a current density of 0.1 A g -1 The cycle performance at 10 cycles and the Rct results of the EIS test analysis of the material after 10 cycles. The specific data results are shown in Table 1.
[0056]
[0057] The present invention provides an exemplary cycle performance analysis diagram of the MnO / Cu / C composite material prepared in Example 3, as shown in FIG. Figure 4 ,Depend on Figure 4 Analysis shows that through 50 mA g -1 After low current activation treatment, at 100 mA g -1 The specific capacity remains at 192 mAh g after 50 cycles at a current density of -1 , it can be seen that the specific capacity and cycle performance are excellent.
[0058] It can be seen from the data in Table 1 that when the MnO / Cu / C composite material provided by the present invention is used as a cathode material for an aqueous zinc ion battery, the composite material can significantly increase the carrier transmission rate and enable the battery to exhibit excellent electrochemical zinc storage performance.
Claims
1. A MnO / Cu / C composite material, characterized in that: The invention is composed of carbon-coated nano-active components, wherein the nano-active components are composed of nano-copper particles and nano-manganese oxide particles.
2. A MnO / Cu / C composite material according to claim 1, characterized in that: The ratio of the nano copper particles to the nano manganese oxide particles is measured according to a molar ratio of copper to manganese elements of 1:3 to 1:
11.
3. A MnO / Cu / C composite material according to claim 1 or 2, characterized in that: The particle size of the nano copper particles is 10 to 70 nm, and the particle size of the nano manganese oxide particles is 10 to 120 nm.
4. A method for preparing the MnO / Cu / C composite material according to any one of claims 1 to 3, characterized in that: In an inert atmosphere, the copper-based complex and the manganese-based complex are ground and mixed, and then heat treated to obtain a MnO / Cu / C composite material.
5. The method for preparing a MnO / Cu / C composite material according to claim 4, characterized in that: The copper-based complex is selected from copper oxalate and / or copper acetylacetonate.
6. The method for preparing a MnO / Cu / C composite material according to claim 4, characterized in that: The manganese-based complex is manganese acetylacetonate.
7. A method for preparing a MnO / Cu / C composite material according to any one of claims 4 to 6, characterized in that: The molar ratio of the copper-based complex to the manganese-based complex is 1:3 to 1:
11.
8. A method for preparing a MnO / Cu / C composite material according to any one of claims 4 to 6, characterized in that: The heat treatment conditions include: 3 ~ 15 ℃ min -1 The temperature is raised to 550 ~ 750 ℃ at a heating rate and kept at this temperature for 1 ~ 4h.
9. The MnO / Cu / C composite material according to any one of claims 1 to 3 is used as a cathode material in an aqueous zinc ion battery.
Citation Information
Patent Citations
Cu-MnO / carbon nanometer fiber composite material and preparation method and application thereof
CN110085447A